Padrão de germinação de sementes e estabelecimento de mudas de guanandi (Calophyllum brasiliense Cambess.) - Lima, Julia Araujo de (2011)
CHAPTER II: Calophyllum brasiliense Cambess. is a tree, typical of tropical rainforests, with seed germination variable and uneven due to restrictions of the layers of the integument. The objective was to characterize the dormancy of seeds of species by their ability to soak, germination, emergence, distribution of germination over time and the timing and quantifies the evolution of dormancy as fruit matured. Independent experiments in replicated randomized block design and were conducted by testing pre-germination treatments and ripening stages fruits in the tree with pericarp and in ground, without such structured. The sowing of seeds was made in germination boxes with vermiculite or sand and filter papercrafting scrolls. The evaluations daily or at intervals of 7 days were considered germinated seeds with protrusion of radicle, and normal and abnormal seedlings, intact seeds and empty. Of fruits with Uberlândia, germination of the seeds without forehead reaches 81% in 43 days, whereas in intact seeds without pericarp and forehead, the germination is 62% in 104 days. With scarification on the forehead region of the micropylar, without reaching the cotyledons, collected seeds in the soil without pericarp the germination percentage reach 94% and 88% normal seedlings. The unconditioned tests show high germination (between 81 and 100%) and normal seedling (91%), but the woody parts of the forehead hinder their extraction and compromise the integrity of the embryo. The integument the seeds of Calophyllum brasiliense cause physical restriction to water, and barring mechanical output in the radicle region of the micropylar. The evolution of maturity of seeds increased the intensity of seed dormancy. Thus, the seeds should also be harvested in the tree when tests show color from yellow to light brown. CHAPTER III: Depending on capacity of Calophyllum brasiliense on expressing diversity and genetic variability among and within populations, the objectives were to characterize and analyze such variability on measures of emergence of species, determine magnitude correlations between these measures and assess the ability of plant establishment. In Uberlândia, on the Uberabinha River and Pedras River (Riparian Forest) and Park of Sabiá (gallery forest) were selected 15 individuals of C. brasiliense. Of these, 13 individuals diaspores were used in the experiment of emergency measures conducted in laboratory of seedlings in a randomized design with five replicates of 20 diaspores. For the establishment of plants, fruits from 11 individuals were pulped and separated by individual diaspores and sown in multicellular trays. When the seedlings were about 4 cm in height were transferred to tubes containing 180 cm3 Bioplant ® commercial substrate and 1 g of Osmocote ®. After six months in the nursery, the plants taller than 15 cm were selected and acclimated for 15 days under sun. The experiment was conducted in a randomized block design, with treatments corresponding to 11 individuals with five replications, each plot contained 10 plants in a density of 3 x 3 m depth of 30 cm. The variability of the measures of emergence of C. brasiliense is higher among individuals, mainly in the percentage of germination. The maximum seedling emergence is high, above 90 % without any pretreatment of the seeds, but can spend up to 365 days to reach this percentage. Although C. brasiliense Tues natural occurrence in areas with water saturation, the species has more than 90% survival in dry soil of Savannah after 90 days of deployment, although this plant survival is variable among individuals. CHAPTER IV: The influence of seed size on physiology has been studied with some intensity in several species of field crops, but is uncommon in forest species. Given this need, the objectives were to evaluate the influence of size seeds on germination, seed germination and seedling emergence of Calophyllum brasiliense Cambess. (Clusiaceae) in controlled laboratory conditions and in the greenhouse and, physically characterize fruits and diaspores of a sample individual and multiple individuals of C. brasiliense, to determine the variability in size and fresh weight. The diaspores collected from various individuals, were classified and separated into three ranges of sizes, small (13 to 15.99 mm), medium (16 to 16.99 mm) and large (17 to 21.00). The water content of seeds, the imbibition curve and the mass of a thousand diaspores was determined for each size. These seeds were mounted two experiments, germinating germination and emergence in a greenhouse. Both distributed in a completely randomized design with treatments related to length of seeds, small (13 to 15.99 mm), medium (16 to 16.99 mm) and large (17 to 20.99 mm), with portion comprises 25 diaspores. The evaluations were daily or every seven days considered germinated diaspores with protrusion of the radicle emerged and with any structure above substrate, and normal and abnormal seedlings, diaspores without apparent damage and empty. Still, 100 fruits and diaspores from one and a mixture of individuals were tested for biometric measurements, water content and fresh weight. The average longitudinal and transverse length, fresh weight and water content of seeds was 16.32 mm, 15.44 mm, 1.33 g and 57.15% respectively. The seed germination was hypogeal cryptocotyledonary and, being slow and uneven without influencing the size diaspore. The germination started around the 25th day and continued until 120 days after sowing. The size seeds of C. brasiliense was not considered an indicator of physiological seed quality. For germination, emergence and early growth of seedlings were not influenced by the size seeds.